Neck pain and dysphagia secondary to diffuse idiopathic skeletal hyperostosis of the cervical spine: A case report - Erdem Sultanoğlu, Tuba; Sultanoğlu, Hasan (Journal of Surgery and Medicine, 2019)
Diffuse idiopathic skeletal hyperostosis (DISH), also known as Forestier disease is characterized by calcification and ossification of the soft tissues, mainly ligaments and entheses. DISH is a systemic non inflammatory disease of unknown cause and is considered an underdiagnosed and mostly asymptomatic nonprimary osteoarthritis. This condition is recognized radiologically only. Rarely, large projecting anterior osteophytes result in esophageal impingement and distortion leading to dysphagia. We report the case of dysphagia and neck pain due to DISH of the cervical spine in a 60 year old female. The patient came to the emergency department with neck pain and dysphagia after falling.